SELF-MICROEMULSIFYING DRUG DELIVERY SYSTEMS (SMEDDS): ADVANCES, APPLICATIONS AND FUTURE PERSPECTIVES - Sarita; Ms Jasvir Kaur; Dr. Anu Jindal; Dr Jaswinder Singh; Dr Rajmeet Singh; Dr Satvinder Kaur (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Self-microemulsifying drug delivery systems (SMEDDS) have emerged as promising approaches to enhance the oral bioavailability of poorly water-soluble drugs. This review comprehensively explores the fundamentals, formulation considerations, characterization techniques, applications, and future perspectives of SMEDDS. SMEDDS are isotropic mixtures of oils, surfactants, co-surfactants, and drug substances that spontaneously form oil-in-water microemulsions upon gentle agitation in the gastrointestinal tract. The review discusses the critical formulation parameters, including the selection of appropriate excipients, optimization strategies, and stability considerations. Various characterization techniques for evaluating SMEDDS, such as droplet size analysis, zeta potential measurement, and in vitro dissolution studies, are examined. Recent advances in SMEDDS formulations, including supersaturated SMEDDS, solid SMEDDS, and stimuli-responsive SMEDDS, are highlighted. The review also explores the diverse applications of SMEDDS across therapeutic areas, including anticancer drugs, antihypertensives, immunosuppressants, and natural products. Finally, current challenges and future perspectives in SMEDDS research are discussed, emphasizing the need for standardized regulatory guidelines and innovative approaches for commercial translation.